Spór o istotę fundacji - Blicharz, Jolanta (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
Foundation is a distinct category from a social organisation. A distinguishing feature of a foundation is a circumstance that the latter is related to the set of normative elements; consequently, foundation encompasses principles related to this organisational form which – in contrast to membership organizations, i.e. communities of persons deciding on activity of a person and benefiting from belonging to this institution – does not have a specific group of persons who benefit from activity of a foundation.
Keywords: fundacja; organizacja społeczna; organizacja pozarządowa; organizacja pożytku publicznego; sektor pozrządowy